Mediating Role of Brand Image: Competitive Advantage and School Selection Decisions in Islamic Education - Ahmad Syaifudin; Ahmad Rifani (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
Purpose: This research investigates the influence of Digital Marketing and Competitive Advantage on students’ school selection decision at SMA Global Islamic Boarding School (GIBS), Barito Kuala Regency, with Brand Image as a mediating variable. The study addresses the paradox of fluctuating enrollment trends despite the school’s high institutional quality and aggressive digital marketing efforts. Research Methodology: An explanatory quantitative design with a causal approach was utilized. Data were collected from 121 students of SMA GIBS through purposive sampling and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) via SmartPLS 4 software. Results: Empirical findings indicate that Digital Marketing and Brand Image directly and significantly influence the School Selection Decision. Competitive Advantage has no significant direct effect on the Selection Decision but serves as the most dominant predictor of Brand Image. Brand Image fully mediates the relationship between Competitive Advantage and Selection Decision (full mediation), while partially mediating the Digital Marketing–Selection Decision relationship. The structural model explains 61% of Brand Image variance (R² = 0.610) and 42.2% of Selection Decision variance (R² = 0.422). Conclusions: Substantive competitive advantages in educational institutions do not automatically translate into enrollment decisions. The transformation of competitive strengths into a strong brand image is a prerequisite for influencing students’ final choices. Effective digital marketing serves as a dual-pathway driver, directly influencing decisions and indirectly strengthening brand perception. Limitations: This study is geographically constrained to SMA GIBS in Barito Kuala with 121 respondents, which may limit generalizability. The cross-sectional design precludes tracking behavioral evolution, and the R² value of 42.2% for Selection Decision indicates substantial unexplained variance by factors outside the model. Contributions: This article offers an integrative framework synthesizing Digital Marketing and Competitive Advantage as simultaneous antecedents of Brand Image in the educational services sector. It resolves inconsistencies in prior literature regarding the mediating role of Brand Image by demonstrating context-dependent mediation effects in high-involvement decision-making.